Peningkatan Kemandirian Belajar Melalui Pembelajaran Sastra Nusantara Berbasis Pendidikan Karakter Tanggung Jawab - Lizawati, Lizawati; Uli, Indriyana (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
The purpose of this study was to determine the achievement and increase in the independence of literary learning among students through education based learning character responsibility. The research method used is descriptive qualitative with the form of classroom action research. The results of the study obtained an increase in the independence of student learning through character education responsibility. This is seen based on the increase in value from the results of analysis of student learning independence observation sheets that have increased. Judging from the learning outcomes of students of the archipelago literature course. The average student learning independence has increased from 63.57% with good categories in the first cycle to 81.34% in the excellent category in  cycle II. So that in the second cycle the percentage of each aspect of independence in the observation results fulfills the indicators of success.Keywords: independence of learning; literary archipelago; responsibility character education,.